2006
DOI: 10.1063/1.2337356
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale studies of domain wall motion in epitaxial ferroelectric thin films

Abstract: Atomic force microscopy was used to investigate ferroelectric switching and nanoscale domain dynamics in epitaxial Pb͑Zr 0.2 Ti 0.8 ͒O 3 thin films. Measurements of the writing time dependence of domain size reveal a two-step process in which nucleation is followed by radial domain growth. During this growth, the domain wall velocity exhibits a v ϰ exp− ͑1/E͒ dependence on the electric field, characteristic of a creep process. The domain wall motion was analyzed both in the context of stochastic nucleation in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
131
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 47 publications
(87 reference statements)
10
131
0
Order By: Relevance
“…Artificial linear domains are thus "written" in the sample by a scanning tip held at a voltage beyond the switching threshold, while individual nanodomains are created by the application of voltage pulses to a stationary tip. Such nanodomains, whose size depends on both the duration and magnitude of the voltage pulse, as well as the size of the tip itself [77,78], can be as small as a few nm in radius [79], in particular when ultrasharp tips based on carbon nanotubes are used [80,81,82], and remain fully stable in measurements extending over a year [83,84]. While PFM imaging is clearly neither real-time, nor full-field-of-view, information on the switching dynamics and domain growth rates in the sample can nonetheless be obtained from averaging the size of sufficient numbers of these nanodomains written with a particular voltage pulse duration and magnitude.…”
Section: Using Pfm To Study Individual Ferroelectric Domain Wallsmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial linear domains are thus "written" in the sample by a scanning tip held at a voltage beyond the switching threshold, while individual nanodomains are created by the application of voltage pulses to a stationary tip. Such nanodomains, whose size depends on both the duration and magnitude of the voltage pulse, as well as the size of the tip itself [77,78], can be as small as a few nm in radius [79], in particular when ultrasharp tips based on carbon nanotubes are used [80,81,82], and remain fully stable in measurements extending over a year [83,84]. While PFM imaging is clearly neither real-time, nor full-field-of-view, information on the switching dynamics and domain growth rates in the sample can nonetheless be obtained from averaging the size of sufficient numbers of these nanodomains written with a particular voltage pulse duration and magnitude.…”
Section: Using Pfm To Study Individual Ferroelectric Domain Wallsmentioning
confidence: 99%
“…Independently, following magnetooptical studies in ferromagnetic materials [97], detailed analysis of the roughness and growth of individual, artificially-written domain walls in epitaxial Pb(Zr 0.2 Ti 0.8 )O 3 thin films by Paruch et al, Tybell et al [85,98,24] demonstrated non-linear creep motion at low fields, with a dynamical exponent µ = 0.5-0.6, and power-law growth of the relative displacement correlation function B(r) ∼ r 2ζ at small length scales below the ferroelectric sample thickness, with a roughness exponent ζ = 0.25, as can be seen in Fig. 5(a).…”
Section: Nanoscale Observations Of Roughness and Creep Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the applied perspective, this interest derives from their current use in a wide variety of active electromechanical and electrooptical elements in devices such as transducers, actuators, motors, sensors, non-volatile memories, etc. [2][3][4][5][6][7] Similarly, from the physics viewpoint, they provide a system to explore a gamut of functionalities ranging from the motion of elastic interfaces through disordered media and associated scaling laws for domain wall motion, [8][9][10] possibility of localized metal-insulator transitions [11][12][13][14] and order parameter coupling at ferroelectric domain walls, [15][16][17][18] statistical modeling of macroscopic polarization switching by microscopic switching units, [19][20][21][22][23] unique behaviors under spatial confinement, 24,25 and many more. Thus, the study of ferroelectrics has remained pertinent even 90+ years since their initial discovery in a Rochelle salt, in 1921 26 .…”
Section: Summary Introductionmentioning
confidence: 99%
“…17,18 Experimentally, PFM measurements demonstrated that 1-and 2-dimensional defects produce significant pinning of 180º domain walls in ferroelectric films. [19][20][21][22][23][24] The local electric field created by defects and domain wall -domain wall pinning are the major contributions to domain wall pinning. 17,25 It is widely reported that in tetragonal ferroelectrics the domain structures of adjacent grains are correlated due to local strain and electric fields.…”
Section: Introductionmentioning
confidence: 99%